Lowdown dirty criminals [videorecording (DVD)] - Murphy, Paul (Director); Rolleston, James; Austin, Samuel (Actor); Gibney, Rebecca (Dark Sky Films, 2020)
After two friends mess up a job for a small-time crook, they cross paths with an assassin and her two henchmen.